THE INFLUENCE OF FAMILY ECONOMY AND PARENTAL MOTIVATION OF COCONUT FARMERS ON THE CONTINUATION OF CHILDREN'S EDUCATION - Revrano Singal; Henry Tamboto; Amsye Winoka (J-Shelves of Indragiri (JSI), 2026)
The purpose of this study is to determine the influence of motivation and household economics of coconut farmers on the continuation of student knowledge in Amurang sub-district (adjust the research location). The study used a quantitative method by means of a survey through a questionnaire distributed to 40 coconut farmers. Data examination was carried out with multiple linear regression tests using the SPSS program. The research results showed that the motivation unsurhad a significant effect on the continuation of student knowledge with a real value of 0.000 <0.05, a calculated t value of 6.173> t table 2.028. The economic unsuralso had a significant effect with a real value of 0.000 <0.05, a calculated t value of 4.018> t table 2.028. Simultaneously, motivation and economics had a significant effect on the continuation of student knowledge, indicated by a real value of 0.000 <0.05, a calculated F of 1823.238> F table 3.24. The R-squared value was 0.80, meaning 80% of the variation in students' academic progress can be exp lained by motivation and economic variables, with the remaberikutng 20% ​​exp lained by other factors outside this study. Therefore, it can be concluded that the higher the parental motivation and the better the economic condition of the coconut farmer's household, the greater the likelihood of students continuing their education to a higher level.